Intrafollicular thyroid hormone staining in whole-mount zebrafish ( Danio rerio ) embryos for the detection of thyroid hormone synthesis disruption - Rehberger, Kristina; Baumann, Lisa; Braunbeck, Thomas (Fish physiology and biochemistry, 2018)
Endocrine-disrupting chemicals are known to impact multiple hormonal axes of vertebrates, among which the thyroid system is crucial for multiple developmental and physiological processes. Thus, the present study focused on the semi-quantitative visualization of intrafollicular triiodothyronine (T3) and thyroxin (T4) in zebrafish embryos as a potential test system for the detection of disrupted thyroid hormone synthesis. To this end, an antibody-based fluorescence double-staining protocol for whole-mount zebrafish embryos and larvae was adapted to simultaneously detect intrafollicular T3 and T4. During normal development until 10 days post-fertilization (dpf), the number of thyroid follicles increased along the ventral aorta. Concentrations of T4 and T3, measured by fluorescence intensity, increased until 6 dpf, but decreased thereafter. Exposure of zebrafish embryos to propylthiouracil (PTU), a known inhibitor of TH synthesis, resulted in a significant decrease in the number of follicles that stained for T3, whereas a trend for increase in follicles that stained for T4 was observed. In contrast, fluorescence intensity for both thyroid hormones decreased significantly after exposure to PTU. Overall, the zebrafish embryo appears to be suitable for the simultaneous visualization and detection of changing intrafollicular TH contents during normal development and after PTU treatment.